INDONESIA MERUPAKAN NEGARA DAN MASYARAKAT MULTIKULTURAL, BUKAN MAJEMUK - Ola Rongan Wilhelmus (Bahasa Indonesia, 2026)
Many discussions and scholarly literature frequently have some difficulties to distinguish the meaning of the terms "multicultural society" with "plural society." This could happen considering that these two terms are closely related to the issue of diversity. However, the two terms actually have a distinct meaning and concept. The article was written in order to clarify the differences in meaning and concept related to the terms of plural and multicultural society, as well as conducting a scientific discussion about Indonesia as a multicultural, not a pluralistic nation. The research employed a qualitative literature review method. Data were collected from various written sources, then analyzed using a content analysis approach. The results of data analysis revealed that a pluralistic society refers to a group of people comprised of many tribes, ethnicities, and religions living together within a specific political territory, yet systematically separated or segregated. This society lacks of a shared social consensus, allowing social conflicts to occur very frequently. In contrast, a pluralistic society is a society consisting of two or more social groups living together within a specific political territory, maintaining their own cultural identities. Nevertheless, each group can live relatively harmoniously with other groups because of sharing a certain social consensus, established jointly as a guideline for living together. This social consensus essentially emphasizes the so called equality, mutual respect, and appreciation for differences. Indonesia, as an archipelagic nation has thousands of ethnicities and numerous religions and beliefs. Nevertheless, it is more accurately described as a multicultural nation because long before independence, it has recognized equality, developed an attitude of tolerance, and respected differences based on the teachings of Pancasila, Bhinneka Tunggal Ika, and the 1945 Constitution.